URBAN GEOMETRY: CITY SHAPE AND SPATIAL LAYOUT OF 6 INDONESIAN GOVERNMENT CENTERS - Muhammad Fajri Romdhoni; Mahbub Rashid (DIMENSI (Journal of Architecture and Built Environment), 2020)
Indonesia is one of the fastest-growing countries. It has about 50% of the population in the ASEAN region. The country is currently evolving and changing. The recent highlight is the country's plan to create a new capital city – moving from the megalopolitan Jakarta in the Java island to a new remote area in East Kalimantan. However, research on Indonesian cities remains very limited to provide an evidence base for planning a new capital city. A fundamental question arises: Should we plan Indonesia's new capital city following western models, or should we plan the city using traditional Indonesian city patterns?  This paper examines urban geometry to show similarities and differences in the government centers in 6 Indonesian provincial capitals. They are Jakarta, Bandung, Medan, Palembang, Surabaya, and the Special Region of Yogyakarta. The six capital cities will be analyzed and categorized using street grid patterns, street centrality, built-up area and open space distribution, and government center distances. This systematic and quantitative comparison of Cities will define the underlying traits and footprint in these Indonesian cities, and the findings could be considered suggestions and guidelines for the new Indonesian capital city. This study utilizes methods and measures using automation techniques to analyze and classify Indonesian government centers based on street networks and urban geometry. The methods include land use recognition techniques using satellite images; OpenStreetMap (OSM) processed using OSMnx; GIS multi-platform applications to run the spatial analysis. On the one hand, the study should contribute to urban design and capital city planning in Indonesia. On the other hand, it should provide methods for comparative studies of cities in developing countries.